Literature Review: peran vitamin D terhadap inflamasi pada kejadian sindrom ovarium polikistik (SOPK) - Tri Irawati; Yessi Crosita Octaria (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Polycystic Ovary Syndrome (PCOS) is an endocrine disorder affecting 5-18% of women of reproductive age, with a high prevalence in Europe and 1,8-15% in Indonesia. PCOS is often associated with chronic inflammation and vitamin D deficiency, which can exacerbate symptoms and increase the risk of cardiovascular disease due to the anti-inflammatory effects of vitamin D.Objectives: To determine the role and most effective dosage of vitamin D in reducing inflammatory markers through a literature review. Methods: The methodology employed is a Systematic Literature Review using the PRISMA method. A search in the Google Scholar, ScienceDirect, and Scopus databases yielded 1,046 articles, of which 7 RCT articles were selected for analysis. The selected articles investigate the effects of vitamin D on inflammation in PCOS, with a total population of 434 participants, published between 2019 and 2024, and were deemed suitable using The Joanna Briggs Institute (JBI) Critical Appraisal method. Results: Out of seven randomized controlled trials (RCTs), five showed that vitamin D supplementation reduced levels of inflammatory biomarkers such as hs-CRP in patients with PCOS. Results varied depending on the dosage, but two specific dosages of vitamin D supplementation 4,000 IU and 50,000 IU showed potential as adjunctive therapy for managing PCOS. Conclusion: Vitamin D supplementation is effective in reducing inflammation in PCOS and has potential as a beneficial adjunctive therapy with positive implications for the long-term health of patients. Dosages of 4,000 IU per day and 50,000 IU every two weeks have been proven effective in reducing PCOS-related inflammation. However, due to the limited number of studies reviewed, the most effective combination of micronutrients to be used alongside vitamin D has yet to be determined.KeywordsInflammation, Polycystic Ovary Syndrome,  vitamin D